PEMBERDAYAAN PELAYANAN PUBLIK - Awang Anwaruddin1 (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2006)
The most protruding weakness of local government bureaucracy in Indonesia from the governance perspective is the rule-driven or rule-following character. This happens as the autonomous and local self-governance has not practically been implemented ever since the Independence Day in 1945. Before the local autonomy policy came into effect on 1 January 2000, the role of local governments was merely as the interest articulation and representative of upper (provincial and central) governments. Such character and role, of course, did not meet the competitive and public-centered spirit within public service program. The implementation of public service policy was then colored by long-chained bureaucratic procedures (red-tape bureaucracy), monotonous and unprofessional system, and inconsistent and unresponsive manner toward the demands of local society. Therefore, local government bureaucracy should change to be more creative and innovative. It should continuously be improved to implement public service delivery programs as well as to find better solutions over complicated problems in the field of public service delivery. A strategic step to overcome the issue is to implement the empowerment approach to local society as mostly applied in the business-model service.